North American river otters consume diverse prey and parasites in a subestuary of the Chesapeake Bay - Wise, Calli M.; Serfass, Thomas L.; Palmer, Emma M.; Yisrael, Leone; Burton-Reeder, Karson; Pagenkopp Lohan, Katrina M. (Frontiers in Mammal Science, 2025)
IntroductionThe North American river otter (Lontra canadensis) occurs from freshwater to marine habitats across North America, yet very little information exists regarding the biology and ecology of river otters residing in the largest estuary in the United States, the Chesapeake Bay.MethodsWe characterized latrines and collected scat to non-invasively examine the diet of river otters residing along 12km of the shoreline of the Rhode River, a tidally influenced subestuary of the Chesapeake Bay.ResultsWe found and assessed characteristics of 18 latrines, which were compared to habitat models of characteristics of latrines in riverine habitats. Scat was examined microscopically and genetically to assess consumed prey and parasites potentially infecting these river otters or their prey. Our results indicate high similarity of latrine characteristics in both tidally influenced and riverine habitats. Additionally, coastal otters appear to readily use manmade structures as latrines. Our results also indicate that river otters consume a wide range of terrestrial and aquatic fauna, primarily consisting of finfish and crustaceans, but also including frogs and ducks. Finally, multiple parasite species were identified, including parasites of river otters and those infecting prey, indicating that parasites likely play an important role in both prey availability and otter health.DiscussionThis study is the first to characterize river otter latrines and diet in a tidally influenced estuarine habitat within the Chesapeake Bay, a critical step in expanding the ecological research of this apex predator across the increasingly urbanized Chesapeake Bay.